Motherhood - Heti, Sheila, 1976- (Henry Holt and Company, 2018)
From the author of How Should a Person Be? How Should A Person Be?Motherhood is a courageous, keenly felt, and starkly original novel that will surely spark lively conversations about womanhood, parenthood, and about how?and for whom?to live.